Features of local anesthesia and innervation of the chin region on the mandible in elderly patients (Эндодонтия Today, 2020)
The increase in life expectancy leads to a progressive increase in the proportion and number of people aged 65 years and older attending dentist. However, along with the number of visits, increases as the number of comorbidities, and the morphological and functional changes in the body. The aim of the study was to investigate the characteristics of the innervation of the anterior mandible and clinical efficacy conduction anesthesia chin near the hole with a 3% mepivacaine local anesthetics in the treatment of dental caries and inflammatory diseases of the pulp in the elderly patients. The anatomical study of the anterior mandible in the age aspect included preparation of the chin area using own methodology staining neurovascular studied 100 preparations received from unidentified persons aged 60-75 years with no abnormalities of maxillofacial region. Research allowed to clarify and describe the features of the innervation of the anterior part of the lower jaw in the area of the apical foramen of the teeth.